DIGITAL ECONOMY REGULATION IN DEVELOPING COUNTRIES: A SYSTEMATIC LITERATURE REVIEW ON CONSUMER PROTECTION, PLATFORM TAXATION, AND LEGAL CERTAINTY IN CRYPTO TRANSACTIONS - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The digital economy is growing rapidly in developing countries but faces complex regulatory challenges across three key pillars: consumer protection, taxation of digital platforms, and legal certainty regarding crypto transactions. This study employs a literature review methodology. The findings indicate that only a few countries have specific consumer protection regulations for digital financial services, Indonesia’s digital economy tax revenue reached Rp31.05 trillion by November 2024, and legal uncertainty surrounding crypto creates a high-risk environment for retail investors. In conclusion, developing countries require a holistic approach that updates consumer protection laws for digital transactions, establishes online dispute resolution (ODR) mechanisms, integrates technology into tax systems, enhances consumer digital literacy, and facilitates regional regulatory harmonisation within ASEAN as well as the OECD’s global digital tax framework. Indonesia emerges as a progressive case study with regulatory reforms treating crypto as an investment commodity and a tax rate increased to 0.21%, yet cross-border implementation challenges and weak digital literacy remain major obstacles to the sustainability of an inclusive and secure digital economy.